Edukasi Gizi Seimbang Berbasis Isi Piringku dan Inovasi PMT Lokal sebagai Strategi Pencegahan Stunting di Desa Kotabaru Kabupaten Banggai - Wijianto Wijianto; Nasrul Nasrul; Sri Musriawati Hasan; Nur Eli Asomah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Stunting remains a major health problem, particularly in rural areas, including Kotabaru Village, Lamala District, Banggai Regency. Low public nutrition knowledge and limited utilization of local foods are contributing factors that exacerbate the risk of stunting in toddlers. This community service activity implemented nutrition education services based on the Isi Piringku guidelines and training in preparing local food-based Supplementary Feeding (PMT) as a preventive intervention strategy. The objective of the activity was to improve the knowledge and skills of the community, particularly mothers of toddlers and integrated health post (Posyandu) cadres, in providing balanced nutritious food to prevent stunting. The activity was held on August 2, 2025, in Kotabaru Village, involving 37 participants consisting of mothers of toddlers, pregnant women, Posyandu cadres, and community leaders. The implementation method included nutrition education, interactive training in preparing local PMT menus, and mentoring. Evaluation was carried out through pre- and post-tests to measure knowledge gains, and observation of PMT preparation practices to assess participant skills. The results of the activity showed an increase in participants' nutritional knowledge and an increase in participants' skills in preparing local food-based PMT menus according to balanced nutrition standards. Another output, a local PMT recipe module, has been produced as a sustainable guide for cadres and families. This activity demonstrates that the Isi Piringku (My Plate)-based nutrition education approach, combined with the use of local foods, is effective in improving nutritional literacy and community skills, and has the potential to support sustainable stunting reduction programs at the village level.